SAYS ISLAMIC CULTURE: FROM THE CRISIS OF LOGIC TO RELIGIOUS DRINKS - Adilya Al Akbar (Religio Education, 2022)
Humans as social beings certainly have their own group which later becomes a social society. And in it there must be a culture and belief that develops in each of these societies. The logic that develops among the people is not uncommon to experience errors , mistakes, or can even be called a logic crisis. So that certain people misinterpret something and actually commit immorality from the misuse of logic without a religious basis. The research method used is descriptive method with a qualitative approach. The results of the study indicate that the community agrees that there are often logical errors in the intersection of culture with religion which eventually leads to normalizing the immorality around them because of the logic crisis that is increasingly happening.